Semiotic Analysis and Ethnography Study on the Implementation of Local Wisdom in Economic Field at Luwu Society - Edi Indra Setiawan; Masruddin Masruddin; Zainuddin Zainuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to dig deeper into how the values of local wisdom in Tana Luwu are implemented into economic activities in the Tana Luwu community. Taking place in Wotu District, East Luwu Regency, the local wisdom in the economic field studied is in the community who work as fishermen and traders there. This research uses ethnographic methods by going directly into the field and describing in real terms the economic activities that occur. The results showed that the noble values of local wisdom such as warani (brave), This is illustrated by the process of fishermen installing rompong, or coconut fronds (cicciri); Adele (fair), illustrated by the process of distribution of panjalae or fishermen, this fair nature is also held by traders without discriminating consumers; Sinunu (cooperating), seeing in the process of going to sea requires teamwork and cooperation; Malabo (generous), seen in the distribution of seafood that attaches importance to the distribution to the entire crew, this is still going on even though the distribution remains proportional; and Sisitappari (mutual trust), This is also illustrated by the process of fishermen installing rompong, or coconut fronds (cicciri). The values of local wisdom are still maintained from generation to generation and are reflected in the economic activities of the people in Tana Luwu, especially in fishermen and traders. In addition, there are also rituals such as the calculation of the moon in determining good and bad days in starting a business and carrying out economic activities. Some of the challenges found in this study are first, the high influence of changing times that enter areas that erode the values of existing local wisdom. Starting from lifestyle, technology, internet and other globalization activities. Second, the lack of desire and enthusiasm of the younger generation to learn and want to inherit economic activities that contain noble values of local wisdom. Among them is because some informants say it is no longer suitable for the needs of the times and is very traditional. Third, there is still a lack of activities to maintain the values of local wisdom by the local government. This is illustrated by the lack of activities that are able to socialize the values of local wisdom.